Campylobacter jejuni bacteremia in a patient with asplenia and enteritis (2019)
ABSTRACT: Campylobacter bacteremia is an unusual presentation of a common infectious disease such as enteritis. We provide key teaching points about its presentation, risk factors, diagnosis and treatment